THE EFFECT OF THE WINDOW-TO-WALL RATIO ON COOLING ENERGY USAGE AND COMFORT TEMPERATURE - Aris Budhiyanto (Dimensi: Journal of Architecture and Built Environment, 2017)
This study presents an investigation of the effect of building envelope, especially glass facade buildings on cooling energy usage and thermal comfort. An office building was modeled with various window-to-wall ratio (WWR) using panasap glass with SC=0.58 in order to analyze the effect of the WWR addition on cooling energy usage and comfort temperature. The result suggested that the average increase of the cooling energy usage is about 5.67% per 10% WWR addition, and of the operative temperature ranges from 0.350C to 0.560C per 10% WWR addition. Moreover, the building with above 20% WWR doesn’t provide comfort temperature.